1999
DOI: 10.1007/s003300050776
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous catheter and guidewire fragmentation with local administration of recombinant tissue plasminogen activator as a treatment for massive pulmonary embolism

Abstract: The purpose of this article is to report four patients with massive pulmonary embolism treated with percutaneous catheter and guidewire fragmentation and local administration of recombinant tissue plasminogen activator (r-TPA). Four patients with massive pulmonary embolism initially underwent pulmonary angiography. Thrombus fragmentation was performed with both standard angiographic guidewires and catheters followed by local infusion of 41-200 mg of r-TPA. Pulmonary angiography was repeated after treatment. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
0
13
0
5
Order By: Relevance
“…For PE with RHTE, case reports and case series have documented resolution of RAT using a glycoprotein IIb/IIIa receptor antagonist (abciximab) with concurrent heparin administration 70 and endovascular embolectomy with basket retrieval through a femoral approach, respectively. 71,72 Catheter thrombectomy, with 73 or without [74][75][76][77] local thrombolysis, has been shown to permit rapid RV recovery following fragmentation. Advantages of the latter strategy include avoidance of major surgery in high-risk patients and a decreased risk of bleeding.…”
Section: Catheter-directed Thrombolysismentioning
confidence: 99%
“…For PE with RHTE, case reports and case series have documented resolution of RAT using a glycoprotein IIb/IIIa receptor antagonist (abciximab) with concurrent heparin administration 70 and endovascular embolectomy with basket retrieval through a femoral approach, respectively. 71,72 Catheter thrombectomy, with 73 or without [74][75][76][77] local thrombolysis, has been shown to permit rapid RV recovery following fragmentation. Advantages of the latter strategy include avoidance of major surgery in high-risk patients and a decreased risk of bleeding.…”
Section: Catheter-directed Thrombolysismentioning
confidence: 99%
“…Death may ensue within minutes due to cardiotoxic and neurotoxic agents in the venom that can produce ventricular arrhythmias and cardiac arrest, and respiratory failure, respectively. In a retrospective review of 12 serious cases [47][48][49][50][51], pulmonary edema was a regular feature after an initial phase of mild skin pain followed 30 min after the sting by considerable muscle pain and cramps, tachycardia and hypertension. At a mean time of 14 h (range 1.5~18 h) after the sting pulmonary edema was evident radiologically and in some cases was associated with hypokinetic cardiac dysfunction, reduced cardiac output and raised serum cardiac enzymes.…”
Section: Systematic Symptomsmentioning
confidence: 99%
“…Several authors have convincingly demonstrated that pulmonary artery thrombus burden can be reduced by mechanical thrombus fragmentation using catheter devices with or without local thrombolysis, thereby ensuring rapid right ventricular recovery [41, 42, 43, 44, 45]. There are no data as to whether this approach is more effective than systemic thrombolysis.…”
Section: Mechanical Thrombus Fragmentation With or Without Local Thromentioning
confidence: 99%